2021
DOI: 10.1186/s41938-021-00406-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indigenous isolates of Beauveria bassiana (Balsamo) Vuillemin (Deuteromycota: Hyphomycetes) against the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae)

Abstract: Background The Colorado potato beetle (CPB) Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) is one of the most damaging pests of potatoes all over the world as well as in Turkey. Both adults and larvae of this pest feed on the foliage of potatoes, and often cause complete defoliation of potato plants, with considerable yield losses of up to 60%. Chemical control of this pest has induced the selection of resistant CPB populations and negative environmental impact. The aim of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This could indicate that the strains are genetically similar and that the sampling site has a relatively low effect when strains are selected naturally via the same host species. Results of a recent study [38] demonstrated significant differences in virulence among B. bassiana isolates obtained from the soil by bait method; nevertheless, genetical analysis revealed that all tested isolates had 99% evolutionary homology with other B. bassiana isolates from the NCBI database.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This could indicate that the strains are genetically similar and that the sampling site has a relatively low effect when strains are selected naturally via the same host species. Results of a recent study [38] demonstrated significant differences in virulence among B. bassiana isolates obtained from the soil by bait method; nevertheless, genetical analysis revealed that all tested isolates had 99% evolutionary homology with other B. bassiana isolates from the NCBI database.…”
Section: Discussionmentioning
confidence: 87%
“…While in the youngest larval instars the LC 50 values for the NDBJJ-BFG strain of B. bassiana were 10 5 -10 6 , in adults the LC 50 values ranged between 10 7 and 10 8 spores/mL [37]. The highest sensitivity of the 1st and 2nd instar CPB larvae was confirmed by a recent study when some of 14 Turkish B. bassiana isolates applied at a concentration of 1 × 10 7 conidia per mL caused mortality between 96.7 and 100% while they caused lower mortality in eggs and adults [38]. Higher vulnerability of early instars towards B. bassiana is not unique for CPB as it has also been reported for some other insect pests [54,55].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, in another study four B. bassiana isolates (BbDm-1, BbDs-2, BbMg-2 and BbMp-1) at 1×10 7 conidia/ml were more pathogenic than the others against L. decemlineata, causing mortality between 97% and 100% on first and second instars, respectively, between 92 and 97% on the third and fourth instars, respectively, and between 93 and 97% on 0-48h adults, respectively, 9 days post treatment. The highest mortality was seen in larvae; but first and second instars were more susceptible to fungal isolates than third and fourth instars (Baki et al, 2021).…”
Section: Introductionmentioning
confidence: 91%